The Masonic Discourse about New Russia: on the Specific Nature of the Fictional Universes in the Russian Masonic Utopias of the 18th Century - Orłowska, Alina (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
The idealistic notions concerning the state and humankind, combined with the criticism of the reality of the time, constituted a significant voice in the late-18th-century discussion about a new vision of Russia. In the utopias by Aleksandr Sumarokov, Mikhail Kheraskov, Vasily Lyovshin and Aleksandr Radishchev the shape of the fictional universe was determined by the belief that the harmonious order destroyed by the imperfection of the human nature can be reconstructed. The authors translated the ideas of freedom, brotherhood and equality into the figurative language of literature, comprehensible both for their fellow Freemasons and for other people. In the eyes of the Russian Freemasons the mythical Golden Age embraced not only the past, but also the future. The recovery of the social order would be guaranteed by a spiritual rebirth of the individual.